Synthesis, characterization, and catalytic properties of AlPO4-40, CoAPO-40, and ZnAPO-40 - Lourenço, J. P. (2013)
The experimental conditions leading to the synthesis of pure and highly crystalline AlPO,-40, CoAPO-40, and ZnAPO-40 have been optimized. Although the preparation of these phases is favored by the presence of TMA+ in the synthesis gel, these ions have not been found incorporated in the final AFR structures. All materials have been characterized by powder XRD, t.g./d.s.c., SEM, EDX, 13C, 27AI, and 3’P solid-state n.m.r., diffuse reflectance u.v.-vis spectroscopy, FTi.r., and catalytic tests using the n-t-xylene isomerization as a model reaction. This multitechnique approach provides strong evidence for the framework incorporation of cobalt and zinc. The acid sites generated by the framework insertion of cobalt and zinc are stronger than those generated by the incorporation of silicon.